Who can afford to dissent at work? The mediating effect of organizational socialization on the relationship between social capital and organizational dissent - Ak, Murat; Turkmenoglu, Mehmet Ali; Acar, Duygu; Ramiz Hacarlioglu, Abdullah; Ozbilgin, Mustafa (Frontiers in Psychology, 2024)
Introduction In today’s interconnected world, fostering a culture of constructive dissent within organizations is more important than ever. Our study sheds light on how social capital—our networks and relationships—affects employees’ ability to express dissent. This study aims to empirically examine whether organizational socialization has a mediating effect on the relationship between social capital and organizational dissent. Methods We utilized surveys to collect data from participants. Quantitative data was collected from 240 employees within the textile in Türkiye. We used structural equation modeling through SmartPLS to test four hypotheses. Results According to the results of the SEM, social capital positively affects organizational dissent. Similarly, social capital positively affects organizational socialization. The mediation level of organizational socialization is at the level of partial mediation on the relationship between social capital and organizational dissent. Based on the results, organizational socialization positively affects organizational dissent. Discussion We contribute to the literature by extending social capital research by illustrating that employees’ social relationships lead to organizational socialization and organizational dissent behavior at work. The results suggest that the ability of employees to show dissent behavior is conditioned by their social capital and mediated by organizational socialization. This research is particularly relevant in sectors with hierarchical structures, where encouraging voice and participation can lead to significant advancements.